An Alternative Cure: The Adoption and Survival of Bacteriophage Therapy in the USSR, 1922–1955. (12th October 2018) - Myelnikov, Dmitriy
Abstract: Felix D'Herelle coined the term bacteriophage in 1917 to characterize a hypothetical viral agent responsible for the mysterious phenomenon of rapid bacterial death. While the viral nature of the "phage" was only widely accepted in the 1940s, attempts to use the phenomenon in treating infections started early. After raising hopes in the interwar years, by 1945 phage therapy had been abandoned almost entirely in the West, until the recent revival of interest in response to the crisis of antibiotic resistance. The use of phage therapy, however, persisted within Soviet medicine, especially in Georgia. This article explains the adoption and survival of phage therapy in the USSR. By focusing on the Tbilisi Institute of Microbiology, Epidemiology and Bacteriophage (now the Eliava Institute), I argue that bacteriophage research appealed to Soviet scientists because it offered an ecological model for understanding bacterial infection. In the 1930s, phage therapy grew firmly imbedded within the infrastructure of Soviet microbiological institutes. During the Second World War, bacteriophage preparations gained practical recognition from physicians and military authorities. At the dawn of the Cold War, the growing scientific isolation of Soviet science protected phage therapy from the contemporary western critiques, and the ecological program of research into bacteriophages continued in Georgia.